The impact of sharing a home with a pet on the physiological state of the human microbiome: a comprehensive study on the Czech population with a focus on filamentous fungi - Wipler, Jan; Čermáková, Zuzana; Buchta, Vladimír; Žák, Pavel; Vlčková, Markéta (Acta veterinaria Brno, 2023)
Czechs commonly share their homes with pet animals. However, the likelihood of transmission of filamentous fungi (FF) between the pet and the owner is not well known. The aim of this study was to define the frequency of such transmission. At the same time, the degree of closeness of owner-animal cohabitation, the effect on the spectrum of shared FF and health risk assessment were defined. The effect of previous antibiotic therapy on fungal flora was also assessed. In total, 150 pet owners and 135 pet animals from 125 households provided 911 samples; 80 non-owners provided 320 samples. All owners completed a questionnaire focusing on the level of contact with the pet and information on previous antibiotic treatment. The relationship between the contact index (CI) and the effect of previous antibiotic treatment on the number of FF species shared was quantified. Results were compared with those of non-owners. The CI was very close (CI > 4) in 131 owners (87.3%). A total of 110 FF were isolated. Common FF were found in 42 households (33.6%); 65 FF were identified in the non-owners. In the last year, 46 pets, 43 owners and 25 non-owners used antimicrobial agents. Aspergillus niger was most prevalent in owners and pets and Alternaria alternata in non-owners. The degree of contact intimacy did not seem to have any effect on the joint abundance of FF, but antibiotic treatment had a significant effect on FF abundance in non-owners. This effect was not significant in either owners or pets.